QUALITY TEST OF FROZEN BUFFALO FROM INDIA REVIEWING FROM Salmonella spp. AT AIKMEL MARKET, DISTRIK OF AIKMEL, EAST LOMBOK DISTRICT, WEST NUSA TENGGARA PROVINCIAL - Abrori, Muh. Muazdzamzam Lil; Mahatmi, Hapsari; Sudipa, Putu Henrywaesa (Buletin Veteriner Udayana; Vol. 14 No. 6 December 2022, 2022)
Since 2015 imports of frozen buffalo meat from India have begun to enter Indonesia, especially in West Nusa Tenggara, as an effort to meet market needs in modern shopping areas in Lombok City. The price of frozen buffalo meat is relatively cheap, causing marketing to expand to the East Lombok area, especially the Aikmel traditional market, which is about 72 km away. This study aims to determine the presence of bacterial contamination of Salmonella spp. on frozen packaged buffalo meat from India sold at Aikmel Market. The research sample was buffalo meat from 10 sellers, each weighing 100 grams. Then isolation and identification were carried out. Bacterial isolation was carried out using selective media, namely Xylose Lysine Deoxycholate , Gram staining, Biochemical Test which included Triple Sugar Iron Agar, Indole, Methyl Red, Voges Proskauer, Citrate and Urease tests. The results showed that samples of frozen buffalo meat marketed in the Aikmel market 9 samples of 10 samples of buffalo meat (90%) showed contamination of Salmonella spp . Based on the results of this study, it is necessary to increase local government supervision of the procedures for selling frozen buffalo meat from India.